Graphene‑based nanofllers and compatibilizers: their infuences on thermal and thermomechanical properties of PBT/PET nanocomposites - Ahmad Saidi, Muhammad Akmal; Lai, Jau Choy; Hassan, Azman; Wahit, Mat Uzir; Anuar, Hazleen (Springer Science and Business Media Deutschland GmbH, 2025)
This study examines the thermal and thermomechanical properties of polybutylene terephthalate/polyethylene terephthalate (PBT/PET) nanocomposites reinforced with graphene nanoplatelets (GNP) and graphene oxide (GO), and compatibilized with maleic anhydride grafted polypropylene (PP-g-MA) and maleic anhydride grafted styrene-ethylene/butylene-styrene (SEBS-g-MA). Differential scanning calorimetry (DSC) showed that PBT/PET blends were miscible in the amorphous region (single Tg) and separated in the crystalline region (double Tm). DSC results indicated increased crystallinity (Xc) in the nanocomposites due to the nucleating effect of the nanofillers, which were dispersed in both PBT and PET phases. However, the addition of compatibilizers slightly reduced the total Xc of the nanocomposites. This reduction is attributed to the interactions between compatibilizers, nanofillers, and the matrix, which restricted chain movement hence, decreasing the crystallinity. Significant enhancements in heat deflection temperature (HDT) were observed relative to the blend, regardless of the compatibilizers used. The maximum HDT was achieved at 1.5 phr for both GNP and GO nanocomposites, with an increase of 41% and 30%, respectively. Dynamic mechanical analysis (DMA) indicated that GNP nanocomposites exhibited maximum 179% higher storage modulus at 30 °C, while GO nanocomposites showed a significant increase by maximum 183%. GNP nanocomposites exhibited a lower tan δ compared to GO nanocomposites, reflecting higher stiffness and restricted chain mobility. It can be concluded that the addition of PP-g-MA enhances stiffness, while SEBS-g-MA improves energy dissipation in PBT/PET nanocomposites reinforced with GNP and GO. These findings highlight their potential applications in industries needing materials with good thermal stability and thermo-mechanical properties.